2012
DOI: 10.1097/psy.0b013e318273bf33
|View full text |Cite
|
Sign up to set email alerts
|

Neural Dysregulation in Posttraumatic Stress Disorder

Abstract: Objective Convergent neuroimaging and neuropsychological research demonstrates disrupted attention and heightened threat sensitivity in PTSD. This might be linked to aberrations in large-scale networks subserving detection of salient stimuli, i.e. the salience network (SN), and stimulus-independent, internally-focused thought, i.e. the default mode network (DMN). Methods Resting state brain activity was measured in returning veterans who served in Iraq or Afghanistan with (n=15) and without PTSD (n=15) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
216
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(245 citation statements)
references
References 67 publications
26
216
3
Order By: Relevance
“…We support and extend these findings by showing that this hyperactivation is particularly important for persistence of PTSD. Furthermore, structural (Long et al, 2013) and functional resting state connectivity studies (Sripada et al, 2012) have revealed increased connectivity within the salience network in PTSD patients. A recent graph analysis study showed a relationship between insula decoupling and reexperiencing symptoms in PTSD patients, indicating disrupted salience determination (Spielberg et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…We support and extend these findings by showing that this hyperactivation is particularly important for persistence of PTSD. Furthermore, structural (Long et al, 2013) and functional resting state connectivity studies (Sripada et al, 2012) have revealed increased connectivity within the salience network in PTSD patients. A recent graph analysis study showed a relationship between insula decoupling and reexperiencing symptoms in PTSD patients, indicating disrupted salience determination (Spielberg et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…(2012), for conflicting findings). Among patients with PTSD, however, it is more common to observe disruptions in DMN integration (Bluhm et al., 2009; Rabellino et al., 2015; Sripada et al., 2012) where it has been proposed that early‐life trauma disrupts the integration of the DMN (Daniels et al., 2010). Despite having a history of trauma exposure, the primary diagnosis among our patient sample was MDD, and the timing, type, and frequency of trauma were heterogenous among participants.…”
Section: Discussionmentioning
confidence: 99%
“…Putative neural mechanisms underlying their pathogenic effect may involve a combination of a hyperactive emotional reactivity system coupled with dysfunctional regulatory circuitry in the frontal lobes (Etkin & Wager, 2007; Hayes, Hayes, & Mikedis, 2012; Pitman et al, 2012). Beyond the fronto-limbic circuitry, aberrations between and within (Sripada et al, 2012) the default mode network (DMN), salience network (SN), and the central executive network (CEN) were demonstrated in PTSD. The DMN and CEN were found to be weakly interconnected and hypoactive, hypothetically destabilized by an overactive and hyper-connected SN and a low saliency perception threshold, along with inefficient DMN-CEN modulation (Akiki, Averill, & Abdallah, 2017).…”
Section: Introductionmentioning
confidence: 99%